Is silicon beneficial for cassava (Manihot esculenta Crantz)? - Barhebwa, F.; Li, Z.; Bragad, C.; Vanlauwe, B.; Delvaux, B. (Springer, 2024)
Background and aim Ranked among the world’s top ten crops, cassava (Manihot esculenta Crantz) is the main staple food in sub-Saharan Africa. Its production is strongly limited by biotic and abiotic stresses, which proved to be mitigated in other plants by silicon (Si) uptake. The role of Si is unknown in cassava. Yet it has genes encoding specific aquaporins involved in plant water and Si influxes in numbers similar to those of some Si accumulating monocots.